Treatment of nocturnal asthma with nedocromil sodium. Issue 12 (December 1994) - Clancy, L; Keogan, S
Abstract : BACKGROUND–The association of nocturnal asthma symptoms with a diurnal increase in inflammatory activity suggests a role for anti-inflammatory therapy in nocturnal asthma. METHODS–Fifty patients with asthma with nocturnal symptoms entered a randomised, double blind, placebo controlled, crossover study. After a two week baseline period patients received nedocromil sodium (4 mg) or placebo four times daily. After eight weeks of treatment patients crossed to the alternative treatment for a further eight weeks. Symptom severity was recorded on a scale of 0-4 and inhaled bronchodilator use and peak flow (PEFR) were also recorded daily by the patients. Asthma severity, pulmonary function (FEV1, PEFR, FVC), and adverse events were recorded at clinic visits (baseline and after four and eight weeks of treatment). Global effectiveness was rated by clinician and patient, and treatment preference was recorded. RESULTS–Efficacy was assessed from data from 28 patients. Night-time asthma (mean (SE) difference between nedocromil sodium and placebo: -0.52 (0.13)), total nocturnal symptom severity defined as night-time asthma plus morning tightness (-0.72 (0.20)), and night-time bronchodilator use (-0.62 (0.23)) were reduced with nedocromil sodium compared with placebo treatment during the primary efficacy period (weeks 5-8) and during weeks 1-4 (-0.36 (0.12), -0.63 (0.20), and -0.55 (0.28), respectively). Morning and evening PEFR values improved slightly–but not significantly–compared with placebo. Patient and clinician opinions favoured nedocromil sodium treatment. Daytime asthma, daytime cough, and clinic assessment of asthma severity (secondary efficacy variables) were improved with nedocromil sodium treatment; day-time bronchodilator use and clinic pulmonary function were not. CONCLUSIONS–Nedocromil sodium was more effective than placebo in reducing nocturnal symptoms of asthma and bronchodilator use in this group of patients.